1996
DOI: 10.1046/j.1365-2141.1996.446981.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta2‐glycoprotein I in thrombosis: evidence for a role as a natural anticoagulant

Abstract: Although the physiological role of beta2-glycoprotein (B2GPI) is unknown, in vitro evidence indicates that B2GPI may be a natural anticoagulant. In this study we have examined whether fluctuations of plasma B2GPI occur in in vivo coagulation. Serial measurements of B2GPI and other anticoagulant proteins were performed in 51 patients with thrombotic (group 1: six patients with disseminated intravascular coagulation (DIC), group 2: venous (n = 4) or arterial (n = 170 thrombosis) and non-thrombotic disease (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 33 publications
1
53
0
3
Order By: Relevance
“…Although the in vivo function of ␤ 2 GPI has not been investigated in detail, it is known to strongly interact with plasma proteins (20) and play a role in regulating coagulation (12) and immune clearance (13). Recent studies have shown that intravenously injected liposomes containing negatively charged phospholipids rapidly bind ␤ 2 GPI, a result that directly correlated with the clearance rates of the vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the in vivo function of ␤ 2 GPI has not been investigated in detail, it is known to strongly interact with plasma proteins (20) and play a role in regulating coagulation (12) and immune clearance (13). Recent studies have shown that intravenously injected liposomes containing negatively charged phospholipids rapidly bind ␤ 2 GPI, a result that directly correlated with the clearance rates of the vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have raised the possibility that autologous serum proteins might bind PS-expressing cells. Indeed, evidence has been presented suggesting that at least one of these proteins, ␤ 2 -glycoprotein I (␤ 2 GPI), could play a critical role in regulating platelet-dependent thrombosis (12) and clearance of liposomes containing negatively charged lipids (13).…”
mentioning
confidence: 99%
“…As shown in Figure 2C, prothrombin alone had no effect whereas platelet procoagulant activity values were statistically reduced upon addition of β2GPI (p=0.01), in line with the reported anticoagulant effect of this latter protein. 21 Platelet procoagulant activity values obtained with murine IgG, 28F4 or 7F6G were not different from those of the control (unstimulated washed platelets). In the presence of their target, murine monoclonal antibodies induced a significant increase in platelet procoagulant activity compared with the antibody alone.…”
Section: Effects Of Murine Monoclonal Antibodies On Plateletsmentioning
confidence: 95%
“…The binding of beta-2-glycoprotein I precursor and thrombospondin could potentially serve beneficial functions in cell and tissue transplantation. Beta-2-glycoprotein binds to negatively charged phospholipids and inhibits the coagulation cascade [30,31], while thrombospondin-1 is a potent inhibitor of T-cell and dendritic cell activation [32,33].…”
Section: Discussionmentioning
confidence: 99%